ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH DI JAWA TENGAH - Atik Alisti Permitasari, 09.05.52.0046; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2013)
The focus of this study is to analyze the effect of the Gross Domestic Product (GDP), Expenditure, Inflation, Population and Number of Industries of the Local Revenue. The object of this study is Central Java by using secondary data time series in period 2008-2011. The technique of data analysis that used is multiple linear regression equation least squares and test hypotheses using t-statistics. Samples from this research is 35 counties and cities in Central Java. During the observation of the study showed that the data were normally distributed. Based on normality test, multicollinearity, heteroscedasticity test and autocorrelation test was not found the variables deviate in the classical assumption. It shows that the available data has been qualified using multiple linear regression equation models. The results of this study indicate that the Expenditure variable and Amount of Industry not showed significant effect on Local Revenue. Inflation variable has a negative impact on Local Revenue. Gross Domestic Product variable and Population gives a significant positive effect on Local Revenue.Keywords: Local Revenue (PAD), Gross Domestic Product (GDP), Expenditure, Inflation, Population and Total Industry